Epigallocatechin gallate does not accelerate the early phase of liver regeneration after partial hepatectomy in rats - Mezera, Vojtěch; Kučera, Otto; Moravcová, Alena; Peterová, Eva; Červinková, Zuzana (Digestive diseases and sciences, 2014)
BACKGROUND: Two-thirds partial hepatectomy (PHx) is an established model for the study of liver regeneration after resection. This process is accompanied by oxidative stress. AIMS: In our study, we tested the effect of epigallocatechin gallate (EGCG), a green tea antioxidant, on the early phase of liver regeneration after PHx. METHODS: Male Wistar rats were divided into five groups: (I) laparotomy + water for intraperitoneal injections, (II) laparotomy + EGCG 50 mg/kg body weight, (III) PHx + water for injections, (IV) PHx + EGCG 20 mg/kg and (V) PHx + EGCG 50 mg/kg, for 3 consecutive days. The rats were killed 24 h after surgery. Biochemical analysis of rat sera was performed. Histological samples were stained with hematoxylin & eosin and bromodeoxyuridine (BrdU). In hepatectomized rats, we also measured plasma malondialdehyde, tissue malondialdehyde, glutathione and cytokines levels, the activity of caspases 3/7, expression of Nqo-1 and HO-1 genes at the mRNA level, and expression of p21, p-p27 and p-p53 genes at the protein level. RESULTS: We observed lower accumulation of BrdU in group V when compared to groups III and IV. The activity of caspases 3/7 and expression of p-p53 were lower in group V than in groups III and IV. Tissue levels of IL-6 were lower in group V when compared to group III. Significant differences were not noted in other parameters. CONCLUSIONS: Administration of EGCG did not stimulate early phase liver regeneration in rats after PHx. There was even lower DNA synthesis in the group treated with a high dose of EGCG.
Keywords: messenger RNA; katechin; regenerace jater; Rats; Antioxidants; Heme Oxygenase-1; cytokiny; Gene Expression Regulation; NAD(P)H Dehydrogenase (Quinone); Rats, Wistar; kaspasy; mužské pohlaví; hepatektomie; Oxidative Stress; NAD(P)H dehydrogenasa (chinon); Cytokines; Hepatectomy; krysa rodu Rattus; hemoxygenasa-1; Cell Cycle Proteins; Caspases; antioxidancia; regulace genové exprese; Liver Regeneration; Catechin; proteiny buněčného cyklu; RNA, Messenger; zvířata; potkani Wistar; oxidační stres; Male; Animals